Discussion Regarding the Development of Lake Toba Geopark Tourism and Inter-Regional Cooperation with the Management Agency Toba Caldera UNESCO Global Geopark - Posma Sariguna Johnson Kennedy Hutasoit; Suzanna Josephine L Tobing; Rutman Lumbantoruan; Ktut Silvanita Mangani; Ricky Martin Manullang (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
The establishment of the Toba Caldera as a UNESCO Global Geopark provides opportunities for local village communities to promote culture and local products and create wider employment opportunities. The purpose of this community service activity is to gain an understanding of the importance of inter-regional cooperation in the development of the UNESCO Global Geopark Toba Caldera tourist area. This inter-regional cooperation can provide sustainable growth, thereby increasing the welfare of local communities. The activities were carried out by visiting the UNESCO Global Geopark Toba Caldera Management Agency, especially at the Samosir Regency Regional Government Office. The development of the Lake Toba area needs to be carried out jointly with the eight regencies around the Lake Toba area in an integrated and sustainable manner, and it cannot work alone. For example, in procuring and repairing roads as entrances to tourist areas, especially tourist villages in the Lake Toba Region. No region can provide for itself because each region has advantages and disadvantages that can be mutually beneficial through good cooperation. Keywords: Geopark, Toba Lake, Toba Caldera, Regional Cooperation, North Sumatra